S-layer protein of Lactobacillus acidophilus ATCC 4356: purification, expression in Escherichia coli, and nucleotide sequence of the corresponding gene. - Boot, H J (1993)
The cell surfaces of several Lactobacillus species are covered by a regular layer composed of a single species of protein, the S-protein. The 43-kDa S-protein of the neotype strain Lactobacillus acidophilus ATCC 4356, which originated from the pharynx of a human, was purified. Antibodies generated against purified S-protein were used to screen a lambda library containing chromosomal L. acidophilus ATCC 4356 DNA. Several phages showing expression of this S-protein in Escherichia coli were isolated. A 4.0-kb DNA fragment of one of those phages hybridized to a probe derived from an internal tryptic fragment of the S-protein. The slpA gene, coding for the surface layer protein, was located entirely on the 4.0-kb fragment as shown by deletion analysis. The nucleotide sequence of the slpA gene was determined and appeared to encode a protein of 444 amino acids. The first 24 amino acids resembled a putative secretion signal, giving rise to a mature S-protein of 420 amino acids (44.2 kDa). The predicted isoelectric point of 9.4 is remarkably high for an S-protein but is in agreement with the data obtained during purification. The expression of the entire S-protein or of large, C-terminally truncated S-proteins is unstable in E. coli.